EFFECT OF PLANT GROWTH REGUALTORS ON THE GROWTH OF VIGNA RADIATA L - AMEETA SHARMA; VARSHA AGRAWAL (International Journal of Pharma and Bio Sciences, 2013)
By the application of various concentrations of selected growth regulators viz. NAA, IAA and Kinetin in Vigna radiata L., the experimentation was undertaken with an intention to find out how the seed germination and seedling rise can be influenced. The seed material was collected from the Durgapura Agricultural Research Institute, Jaipur, Rajasthan (India). The seeds were soaked in different concentrations (10, 50, and 100 ppm) of NAA, IAA and Kinetin for 24 hours. Five replicates of each treatment with 10 seeds per replicate were set for accurate analysis. Noteworthy variations were found between all treatments in all germination aspects.